Training cognition : optimizing efficiency, durability, and generalizability - Healy, Alice F.; Bourne, Lyle Eugene, 1932- (Psychology Press, 2012)
"This book describes research on training using cognitive psychology to build a complete empirical and theoretical picture of the training process. It includes a review of relevant cognitive psychological literature, a summary of recent laboratory experiments, a presentation of original theoretical ideas, and a discussion of possible applications to real-world training settings"--Provided by publisher.